Effect of the Use of Video Compact Disc Instructional Package (VCDIP) on the Academic Performance of Junior Secondary School Business Studies Students in Imo State, Nigeria - Marcel, Ezemoyih Chuks; Nweze, Tina; Uwakwe, Theresa Nnenna (World Journal of Vocational Education and Training, 2019)
The study was aimed to examine the effect of video compact disc instructional packages (VCDIP) on the academic performances of Junior Secondary School Business Studies students in Owerri, Nigeria. A quasi-experimental design was used. The subjects were randomly placed into two treatment group. Treatment “Group A (Jss2A) was made up of 40 (15 males and 25 females) students exposed to VCDIP, while “Group B (JSS2C) was also 40 (17 males and 23 females) taught through conventional teaching mode. Three research questions and three null hypotheses guided the study. A copy of a 50 item researcher made questions and a copy of 10 affective response questionnaire were validated and used. A reliability index of 0.81 and 0.80 were calculated for the first and second instruments for the study using Kuder Richardson (KR – 21) and Pearson “r” respectively. The data were analyzed using mean, t-test and ANOVA. The study revealed that the students exposed to VCDIP performed slightly better than the conventional group. This implies that VCDIP can be effectively used as both supplementary material to the teacher and as alternative mediated self-instructional package to the learner.